Heroism and the Pursuit of a Meaningful Life. (July 2019) - Kinsella, Elaine L.; Igou, Eric R.; Ritchie, Timothy D.
Individuals and groups of individuals are motivated to find meaning in their activities and in life, generally. That is, when events or affective states threaten or reduce a person's sense of meaning, psychological processes are mobilized to serve the goals of meaning maintenance and meaning reestablishment, respectively. We examined two avenues for meaning maintenance: First, we considered psychological resources from the enhancing, moral modelling, and protecting functions of heroes, and second, we considered engagement in heroic behavior as a means to create meaning. We addressed contemporary heroes via conceptual and empirical literatures to discuss a variety of ways that heroes derive meaning from their own actions, and the extent to which others could glean personal meaning from a hero's characteristics and actions. We present a meaning regulation framework that explains how heroes and heroic behavior each boost meaning and the meaning maintenance processes, such as heroism as a buffer against meaning threats. We synthesized relevant literatures on meaning and heroism, and offer a framework that illustrates heroic functions in the context of meaning in life: a central, superordinate psychological variable that is familiar to many individuals and groups. This framework offers many opportunities for future research and practical application of heroism.